(untitled) (Khairulummah, 2023)
Hazrat Maulana Allama Abdul Rasheed Naumani was endowed with many virtues and it can be said that Allah Ta’ala had made him an excellent example of His supremacy in religious mind and an all-round personality. Due to which modern era scholars highly appreciated him. Maulana Naumani was undoubtedly a treasure trove of Islamic knowledge, which was benefited by many scholars, students and the general public. Many of his works, in which "Laghat al-Qur’an" has the same status in Urdu as Imam Raghib’s "Mufardat al-Qur’an" in Arabic. Rather, this book is the source for most of the dictionaries written in Urdu language in terms of its style of writing, references and comprehensiveness. Although there are other books on the subject of Qur’an dictionaries in Urdu language, but this book is of significant importance in terms of its usefulness. That’s why this book is equally useful not only for scholars and students but also for a common and general reader. For all these reasons, bringing his personality and his academic services and the sources and references of the book to the public in a research way is a debt payment as well as a duty fulfillment. For these reasons, I have chosen the personality of Maulana Abdul Rasheed Naumani and the research and critical review of the sources and references of his book "Laghat al-Qur’an" as a topic for my research paper.